Associations of minerals intake with colorectal cancer risk in the prostate, lung, colorectal, ovarian cancer screening trial - Li, Siyue; Ren, Qingqian; Song, Zixuan; Liu, Baixue; Wang, Dan; Shang, Yanna; Wang, Hao (Frontiers in Nutrition, 2024)
Objective Exploring the association between common mineral intake and the risk of colorectal cancer (CRC). Methods We utilized the multivariate Cox proportional hazards model to assess the association between intake of minerals and the risk of CRC, estimating hazard ratios (HRs) and 95% confidence intervals (CIs). Results A total of 101,686 eligible participants were included in the analysis of this study, including 1,100 CRC cases. After adjusting for potential confounders, we found that total zinc intake (HRQ4vs.Q1: 0.79, 95%CI 0.67–0.93; P for trend <0.05), iron intake (HRQ4vs.Q1: 0.81, 95%CI 0.68–0.96; P for trend <0.05), copper intake (HRQ4vs.Q1: 0.80, 95%CI 0.68–0.95; P for trend <0.05), selenium intake (HRQ4vs.Q1: 0.83, 95%CI 0.69–0.98; P for trend <0.05) were significantly negatively associated with the incidence of CRC, but magnesium intake in the appropriate range is associated with a reduced risk of CRC (HRQ3vs.Q1: 0.77, 95%CI 0.65–0.91; P for trend >0.05). Conclusion Our findings suggested that an appropriate intake of total zinc, iron, copper, selenium and magnesium were associated with lower CRC risk.